Electric Vehicle Modeling in MATLAB and Simulink with SoC &SoE Estimation of a Lithium-ion Battery. Issue 1 (April 2021) - Chatterjee, P; Singh, J; Singh, R; Avadh, Y A R; Kanchan, S
Abstract: To improve the energy storage management system of an electric vehicle, we monitored exact battery states. Here we created different models for BMS management, for thermal modelling, thermal characteristics and EV modelling. We used different drive cycles sources to get our results here, we simulated models for different set of time and got simulation results. The variation in graphs and display lead us to different conclusions that how different parameters affect the performance and efficiency of an electric vehicle. We have presented a simple integrated State of charge (SOC) and State of energy (SOE) estimation technique. By utilizing this technique, the battery SOC and SOE both can be assessed easily rather than processor computational difficulty in BMS.